Film watching habits of journalism students from the perspective of the theory of utilities and satisfaction - Vujović Marija; Obradović Neven (CM. Communication and Media)
Films are the most popular and most visited cultural program in Serbia. According to research by the Institute for the Study o f Cultural Development, the largest audience group in Serbia is the cinema audience. In this paper, film is viewed as a medium, but also as media content, which has its own active audience. The film watching habits o f journalism students at the Faculty o f Philosophy, University o f Niš, are viewed from the perspective o f the theory o f utilities and satisfaction, and the needs whose satisfaction is investigated in this paper are cognitive, affective, personal integrative, social integrative, and the need for releasing tension. The essence o f the theory o f utilities and satisfaction is the transfer o f power from the hands o f senders to the hands o f recipients o f messages. It no longer matters what the sender o f the message wants to achieve, but what benefits and pleasures the recipients o f the media content have. The audience becomes "active", and the premise "what the media does to people" has turned into "whatpeople do to the media". The research was conducted in January 2023 and included 138 journalism students, from all four years o f undergraduate studies. For the purposes o f the research, a special questionnaire was created as a data collection instrument, and the data obtained were processed using the SPSS statistical data processing program. The results o f the research show that watching movies is a frequent activity for journalism students, that they most often watch movies online, on a computer and/or mobile phone, that most journalism students go to the cinema with friends, and that journalism students cite entertainment and socializing with friends, partners or family as the most common reason for going to the cinema. Comedy is the most common film genre that students watch in the cinema, and the opinion o f friends and acquaintances is the most common reason for choosing a film to watch. The results o f the research also show that journalism students satisfy affective needs and tension release needs the most when watching a film, and personal integrative needs the least.